2021
DOI: 10.3390/jmse9111155
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrodynamic Characteristics Induced by Multiple Layouts of Typical Artificial M-Type Reefs with Sea Currents Typical of Liaodong Bay, Bohai Sea

Abstract: Artificial reefs are effective measures to improve the marine ecological environment and increase fishery production. However, there are several geometries being investigated nowadays and their setup, including the spacing between groups of them, can provide dissimilar effects on hydrodynamics. To enhance the understanding of this topic, in this paper, the focus is mainly on M-Type artificial reefs that will be adopted in Juehua Island, Liaodong Bay, China. An experimental campaign was carried out in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Earlier studies suggested that the existence of artificial reefs appears to have an inhibiting effect on flow propagation (e.g., Shu et al, 2021bShu et al, , 2021cHarris et al, 2021;Gu et al, 2022). The incoming flow velocity abruptly reduced in the front of artificial reefs, and then the flow separation occurred around the top of the first reef (Figure 5).…”
Section: Longitudinal Velocitiesmentioning
confidence: 92%
See 3 more Smart Citations
“…Earlier studies suggested that the existence of artificial reefs appears to have an inhibiting effect on flow propagation (e.g., Shu et al, 2021bShu et al, , 2021cHarris et al, 2021;Gu et al, 2022). The incoming flow velocity abruptly reduced in the front of artificial reefs, and then the flow separation occurred around the top of the first reef (Figure 5).…”
Section: Longitudinal Velocitiesmentioning
confidence: 92%
“…The physical model of different layout spacing of reefs are tested under different flow velocity (i.e., 0.085 m/s, 0.130 m/s, 0.170 m/s, 0.214 m/s, and 0.257 m/ s), meanwhile, the particle image velocimetry (PIV) technology was applied to quantify the flow fields generated around artificial reefs. Detailed information about the experimental protocol and physical model of artificial reefs can be found in Shu et al (2021b;2021c).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different marine organisms have different tendencies towards the strong or weak turbulence fields. Such turbulence intensities around artificial reefs can meet the needs of different biological characteristics (Kim et al, 2014b;Shu et al, 2021b). The affected regions of the turbulent area produced by different types of reefs are varied, which has been discussed by Howe (2003).…”
Section: The Effect Of Flow Fieldmentioning
confidence: 99%